Enhanced d-tagatose production by spore surface-displayed l-arabinose isomerase from isolated Lactobacillus brevis PC16 and biotransformation. (January 2018) - Guo, Qi; An, Yingfeng; Yun, Junhua; Yang, Miaomiao; Magocha, Tinashe A.; Zhu, Jingfei; Xue, Yanbo; Qi, Yilin; Hossain, Zabed; Sun, Wenjing; Qi, Xianghui
Graphical abstract: Highlights: A new strain, L. brevis PC16, producing d -tagatose was isolated and identified. A novel biocatalyst was developed and characterized via surface-displayed L-AI. The immobilized L. brevis L-AI was firstly used in the d -tagatose biosynthesis. A high efficient immobilized method for producing d -tagatose was established. Abstract: In the present study, a new strain of Lactobacillus brevis producing d -tagatose was isolated and identified. Then, the l -arabinose isomerase (L-AI) of this strain was displayed on the spore surface of Bacillus subtilis DB403 by using an anchoring protein CotG and a peptide linker (Gly–Gly–Gly–Gly–Ser). This displayed L-AI with high specific activity and stability was used as a novel immobilized biocatalyst for producing d -tagatose through batch and semi-continuous biotransformation. The conversion rate of d -tagatose from 125 g/L d -galactose was achieved 79.7% at 28 h, and the volumetric productivity reached 4.3 g/L/h at 20 h. Furthermore, the displayed L-AI showed a good performance on the reusability and remained 87% of the specific activity and 40.7% of the conversion rate after five recycles. A high efficient immobilized method for producing food-grade d -tagatose was established using spore surface-displayed L-AI.